PENGARUH TERAPI MUSIK NATURAL TERHADAP PENAMBAHAN NYERI SAAT SUCTION PADA PASIEN TERPASANG VENTILASI MEKANIK DI ICU - Nabila Tsamara Zahra (2023)
Pain is a person's perception of feelings that are influenced by a stimulus or pathological disease that causes uncomfortable effects. Pain has a different perception in each individual. One of the causes of increased pain is the suction action that is routinely given to critical patients in the ICU. There are various pharmacological and non-pharmacological therapies that can be used to treat the sensation of pain. One of the non-pharmacological techniques that can be used to relieve pain is natural music therapy. Natural music therapy can cause a relaxing effect which can be a distraction from the pain sensation that is being felt by the patient. Purpose: This study aims to determine the effect of natural music therapy on patients' pain scores after suctioning. Methods: This research method used a Quasi Experiment with a pre-post single group design with a total of 30 critical patients attached to a mechanical ventilator in the ICU. Results: The results of the univariate analysis showed that there was an increase in the patient's pain score after suctioning with a significant increase. Bivariate analysis used the Wilcoxon test with the results of the study showing a p value of 0.002 < 0.05 in CPOT observations and a p value of 0.004 < 0.05 in BPS observations. This shows that natural music therapy has an effect on pain scores in critical patients who receive suction in the ICU. Keywords: ICU, suction, pain, mechanical ventilator